2022
DOI: 10.1007/s10708-022-10618-3
|View full text |Cite
|
Sign up to set email alerts
|

Predicting socioeconomic indicators using transfer learning on imagery data: an application in Brazil

Abstract: considerably different, results are consistent with the literature and encouraging as it is a first analysis of its kind for Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Given the lack of traditional data collection methods, it has been proposed to use alternative data sources, such as satellite images. The use of satellite images has proven to be a cost-effective means of obtaining real-time data access in countries where data is inaccessible due to social, environmental, or economic problems [2][3][4] . Satellite images have been used in applications across various domains, including environmental science and conservation for deforestation monitoring 5 , as well as in public health for measuring food security indices 6 , detecting poverty 7,8 and predicting climate-sensitive diseases like dengue 9,10 , or malaria 11 These applications are especially valuable in LMIC with limited resources, benefiting up to 128 economies and public health in the process [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Given the lack of traditional data collection methods, it has been proposed to use alternative data sources, such as satellite images. The use of satellite images has proven to be a cost-effective means of obtaining real-time data access in countries where data is inaccessible due to social, environmental, or economic problems [2][3][4] . Satellite images have been used in applications across various domains, including environmental science and conservation for deforestation monitoring 5 , as well as in public health for measuring food security indices 6 , detecting poverty 7,8 and predicting climate-sensitive diseases like dengue 9,10 , or malaria 11 These applications are especially valuable in LMIC with limited resources, benefiting up to 128 economies and public health in the process [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…In a seminal study, Jean et al [2] [3] extended this work and showed how to fine-tune a deep Convolutional Neural Network (CNN), pre-trained on the ImageNet data, to predict poverty levels from high-resolution daytime satellite images in sub-Saharan Africa. This paper has been followed by many studies, see [4] for a review. However, despite the successes of this approach, the results have yet to be employed for policy decisions.…”
Section: Introductionmentioning
confidence: 99%
“… Castro et al. 59 2022 First, VGG16 CNN (transfer learning). Second, linear regression (combination of ridge and lasso).…”
Section: Introductionmentioning
confidence: 99%